Health insurance in developing countries : willingness to pay for health insurance in Thailand using discrete choice experiment methods - Nanna, Anoo (Curtin University, 2011)
In Thailand, a universal health insurance coverage policy was implemented in 2001 alongside the reform of public health insurance. Since the reform, Thailand has had three major public health insurance schemes of the Social Security Scheme (SSS), Civil Servant Medical Benefit Scheme (CSMBS) and the Gold Card scheme. These three schemes covered more than 90 percent of the Thai population in 2003, moving the country closer to universal coverage.The Gold Card scheme was a new public health insurance scheme, introduced in 2001 and covering the majority of Thai population. The scheme is designed to provide coverage for those on low and middle incomes and, thus, plays a vital role in the drive towards universal coverage. There are problems that need to be rectified in this scheme, including financing feasibility, the need for additional sources of finance and the problems of contracted hospitals in the Gold Card scheme.This thesis seeks to elicit the willingness to pay (WTP) for public health insurance (the Gold Card scheme) in Thailand by using a Discrete Choice Experiment (DCE) approach. DCE provides an interesting application to decision- making in health care financing and this study is the first to use the DCE approach to elicit the WTP for public health insurance in Thailand.WTP may help policy makers understand the communities’ preferences because it is elicited through community consultation. Although insured people in the Gold Card scheme currently pay nothing for accessing health care, the DCE approach finds that insured people may be willing to contribute to the cost of running the scheme through the payment of a premium.The DCE was conducted in the northern part of Thailand from 1st August to 31 October 2009. The sample size comprising 1,200 heads of households from five districts who are covered by the Gold Card scheme were surveyed and interviewed. Both qualitative and quantitative methods were used. Qualitative methods were used to collect socio- economic status, health expenditures, hospitalisation and financing experience. Quantitative methods were used to analyse DCE data.The study finds that the Gold Card scheme is very important for respondents and if the Gold Card scheme is able to extend the choices of health care providers and the waiting time in Out-Patient-Department (OPD) can be reduced, insured people would be willing to pay a premium for the Gold Card scheme.Thus, it is possible that premium payment can be used to raise additional funds for the Gold Card scheme. This study recommends that as long as other additional public funds such as tax reform cannot be sourced, the Gold Card scheme may require the insured to pay the premium in order to ensure its long-term viability.